Charge-voltage relationship of the first impulse corona in long airgaps - Ortéga, P. (2005)
This paper investigates the relationship between the charge Qi of the first impulse corona and the associated inception voltage Ui for a 1 m point-plane airgap submitted to impulse voltages. Experimental studies under both polarities are reported; the Qi-Ui characteristics obtained allow empirical quadratic relationships between these two quantities to be derived. A physical interpretation is proposed by considering the established characteristics of the first impulse corona. The Gauss and Ampère-Maxwell laws can be applied and the quadratic Q i-Ui relationship is justified by the present model. © 2005 IOP Publishing Ltd.